Assessment of knowledge, attitude and practices of epilepsy patients’ towards their illness and treatment in a tertiary care hospital in Kuantan Pahang Malaysia - Rathor, Mohammad Yousuf; Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Mohd Shah, Azarisman Shah; Hasmoni, Mohamed Hadzri; Draman, Che Rosle; Tin, Myo Han (Ibn Sina Trust, 2017)
Patients beliefs determine their response to an illness and its management especially if it is chronic. Studies assessing patient’s knowledge of their epilepsy are scarce. We report the first objective study evaluating knowledge, attitude and practices of epilepsy patients referred to a tertiary care centre in East Coast of Malaysia. Materials and Methods: A cross sectional study using pre-tested, semi-structured questionnaire among consenting epilepsy patients. Results: The demographic details and responses to a questionnaire assessing their insight towards epilepsy were recorded. Among 132 respondents, 51.5% were male and 48.5 % were female. Their age ranged from 14 to 70 years (mean = 31.63 ± 13.41). Majority (53.8%) of them aged equal or less than 30 years. The median number of years they had epilepsy was 8.0 (4.0, 18.8) years and average duration of seizure prior to seeking medical attention was 1.0 (0.3, 4.5) years. The average number of years they were receiving treatment from a hospital was 5.50 ± 5.84. Most (90.9%) did not know the cause of epilepsy; however 93.9 % were aware that it can be treated with modern drugs. While only 22.7 % believed that faith healers can treat epilepsy, 74.2% had tried other forms of treatment. Negative attitude was reflected in the belief that epilepsy is due to supernatural powers (1.5%) and that epilepsy is contagious (17.4 %). Positive attitude included that PWE can take a job (66.7%), allowing a child with epilepsy to study (80%), not objecting children to play with a child with epilepsy (54.5%), marry (65.9%) and having children (58.3%). Conclusions: Patients with epilepsy are not knowledgeable about their disorder. This is true regardless of age, educational background, or number of years with epilepsy. The results suggest that there is a critical need to enhance epilepsy education and improve attitudes towards epilepsy beyond seizure control.